(untitled) (Journal of Pathology of Nepal, 2015)
Background: Gastritis is commonly reported using several parameters such as infiltration by neutrophils, lymphocytes, intestinal metaplasia, atrophy and Helicobacter pylori. In recent years, mast cells are also suggested in several studies to play central role in development of gastritis. This study triedto look at the relation between the mast cell count and infiltration by neutrophils and Helicobacter pylori. Materials and methods: This is a retrospective study which includes endoscopic gastric biopsies received at the histopathology department of GRP polyclinic that have been diagnosed as chronic gastritis. Clinical information regarding associated gastrointestinal symptoms and conditions were obtained from the medical database. Patients taking antibiotics, proton-pump inhibitors, H2- antagonists, nonsteroidal anti-inflammatory drugs or corticosteroids were excluded from the study. Also excluded are patients with dysplasia or carcinoma. Sections were then stained by H&E and Giemsa for the evaluation of H pylori infection and inflammation. These sections were examined by two pathologists. Mast cells were counted in 1000 epithelial cells in 40x.Three different counts were performed by each pathologists and an average score was taken for every case. Results: A total of 534 cases were included in the study. Mast cells were detected in all the cases. However, mast cells were seen mostly in mild grade 321 (60%). Ninty-eight percent of our cases showed H. pylori positivity and 385 (72%) of cases had active gastritis. A positive correlation was found between mast cells density and infiltration by neutrophils as well as Helicobacter pylori infection with significant P value of 0.0001 in each. Conclusions: Mast cells are seen in a significant number of biopsies with gastritis showing positive correlation with neutrophilic infiltration and Helicobacter pylori infection.